Seleção de genótipos de tomateiro para processamento com alto teor de zingibereno resistentes a artrópodos - praga - Lima, Isabela Pereira de (2014)
Despite being a crop very known and cultivated by farmers around the world, the tomato has many pest problems, including the attack of pests such as spider mite (Tetranychus urticae koch.), whitefly (Bemisia tabaci) and tomato pinworm (Tuta absoluta) where main method of control is the chemist. Obtaining resistant cultivars through interspecific crosses between cultivars and wild tomato species such as Solanum habrochaites var hirsutum becomes an important form of control. The S. habrochaites var hirsutum has a high content of allelochemicals zingiberene (ZGB) in their trichomes present on the leaf surface, which promote resistance to arthropod pests that attack the crop . The present study aimed to indirect selection for industrial tomato plants with high levels of ZGB resistant spider mite, whitefly and tomato pinworm and genetic parameters heritage ZGB content in tomato leaflets. It was performed interspecific cross Solanum lycopersicum Redenção x Solanum habrochaites var hirsutum, and the F2 population was quantified ZGB content. In this population were selected genotypes contrasting the content of ZGB, and tested for resistance spider mite and whitefly. Six genotypes were selected for high content (RVTZpl#79; RVTZpl#141; RVTZpl#142; RVTZpl#143; RVTZpl#277; RVTZpl#331) and three low content (RVTZpl#09; RVTZpl#189; RVTZpl#365). The inheritance of the ZGB content presents high heritability with incomplete dominance in the sense of lower values and controlled by 2,24 genes. Plants with high levels of ZGB exhibited the lowest average distance to the mite, oviposition and number whitefly nymphs and oviposition and number tomato pinworm larvae, proving the effectiveness of the high content of ZGB in repellency these arthropods pests.